Equilíbrio de Nash no mercado simultâneo de preços e quantidades : análise da demanda exportadora de carne bovina brasileira - Moraes, Fabrício César de (2016)
The process of globalization has allowed significant growth of commercial interaction between countries. The state of Mato Grosso is benefited from this expansion, with good beef export ratios caused by increasing global demand for goods produced in Mato Grosso. The state of São Paulo is the main competitor in the sector. Assuming that the states act in order to optimize resources, maximizing revenue through taxes, the strategy adopted on prices and quantities is essential to consolidate the leading role in this sector at regional and global level. The purpose is to identify if there is a dominant strategy to explain the state's overall position in the international market, based on the behavior of global demand.